1973
DOI: 10.1085/jgp.61.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Disc Electrophoresis of Extracts from the Taste Buds Located in Circumvallate Papillae of Rat Tongues

Abstract: The epithelium of the circumvallate papillae of rat tongues was stripped off by treatment with 0.005% elastase in a state when many taste buds were present. The taste buds were isolated from the stripped epithelium by further treatment with 0.005 % elastase and 0.08 % trypsin. A protein which was thought to be characteristic of taste buds was found from semimicro disc polyacrylamide gel electrophoretic studies of the stripped epithelia with and without taste buds. This result was supported by micro disc polyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In addition to the failure of the other groups, in direct experimental tests, to substantiate the earlier claims, Koyama and Kurihara (44) showed that the "sweet-sensitive protein" is present in large amounts throughout the bovine tongue epithelium whether or not taste buds are present. Later reports show that unique proteins do exist in preparations derived from taste papillae and taste bud cells (45,46), but their function has yet to be elucidated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the failure of the other groups, in direct experimental tests, to substantiate the earlier claims, Koyama and Kurihara (44) showed that the "sweet-sensitive protein" is present in large amounts throughout the bovine tongue epithelium whether or not taste buds are present. Later reports show that unique proteins do exist in preparations derived from taste papillae and taste bud cells (45,46), but their function has yet to be elucidated.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure reported for isolating rat circumvallate taste buds (Uehara, 1973) differs substantially from our procedure. The rat papillae were digested in a medium containing 0.005% elastase and 0.08% trypsin for a total of 12 hr.…”
Section: Use Of Collagenasementioning
confidence: 98%
“…The epidermal material was collected from the papillae and the taste buds were then excised by dissection with the aid of a dissecting microscope. In the procedure of Uehara (1973), it was intended to isolate whole taste buds, rather than the cells themselves as in the present method. a "Suspended" protein is the amount that was released from the tissue by treatment with a loose-fitting all-glass homogenizer as described in Methods.…”
Section: Use Of Collagenasementioning
confidence: 99%
See 2 more Smart Citations